(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Social infrastructure, which broadly refers to infrastructure/assets that support social services, includes the sectors of education, health and medical care, nutrition, water supply and housing, which contribute to significant improvements in human development while also accelerating economic growth. Karnataka has made rapid strides in the provision of social infrastructure through the implementation of targeted programmes that are supported by ample financial allocation, thereby contributing to multidimensional human development in the State. With this reason the present paper attempts to know about social infrastructure in Karnataka State entitled, “An Economic Analysis of Social Infrastructure in Karnataka”. This study is based on secondary data. Secondary data has been collected from various research papers, magazines, articles, journals and is also based on the published, unpublished and electronic referred sources. Finally present study has intended to offer suitable suggestions according to finding which are found during study.